Pronunciation difficulties confronted in akkaraipattu zonal educational division: a special reference on two selected schools of grade 10 &11 students - Ismail, M.B.M.; Ilmudeen, A. (University of Jaffna, 2012)
The pronunciation is playing a vital role in the field of spoken language. Everybody wants to speak English like a native speaker. But, English pronunciation is always a big problem for them. People can use simple words and grammar structures that make people to understand Language communication. People cannot use "simple pronunciation" when people speak English. The good English pronunciation will make people to understand others’ speech easily. Then, People will be willing to listen to those who communicate. This research paper aims at exploring reasons for pronunciation difficulties confronted by selected school’s students and to solve student’s pronunciation difficulties. Understanding this issue leads to a greater solutions to solve difficulties confronted by the students. Primary Sampling Units (PSU) are Schools that are from two schools such as National School of Addalaichenai and National School of Akkaraipattu in Akkaraipattu Zonal Educational Division. Secondary Sampling Units (SSU) are grade 10 and 11 school students. Researchers have prepared the questionnaire to evaluate students’ pronunciation abilities. Incorrect pronunciation, louder pronunciation than silent pronunciation and quick pronunciation without a stoppage were the pronunciation difficulties faced by students in schools. Fluency in English pronunciation cannot be expected from school children due to several reasons. Mother tongue interference, Inexperience of phonology, Lack of knowledge in English phonetic script, inappropriate teacher’s guidance, lack of practice were identified as reasons for pronunciation difficulties. Since pronunciation played a pivotal contribution in communication students’ skills, careful preparation of students, support from parents and teachers from students’ early stage should be developed among students.
Keywords: Pronunciation; Interference; Phonetic